2022
DOI: 10.3390/s22072602
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient and Effective Deep Learning-Based Model for Real-Time Face Mask Detection

Abstract: Since December 2019, the COVID-19 pandemic has led to a dramatic loss of human lives and caused severe economic crises worldwide. COVID-19 virus transmission generally occurs through a small respiratory droplet ejected from the mouth or nose of an infected person to another person. To reduce and prevent the spread of COVID-19 transmission, the World Health Organization (WHO) advises the public to wear face masks as one of the most practical and effective prevention methods. Early face mask detection is very im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…In this research, we explored vision-based Transformer architecture for SC classification as shown in Figure 2 , where the MVT architecture receives an image as input data with a size of 72 by 72. First, the input image is converted into patches as in [ 55 ]. MVT supports a different number of patches based on the underline scenario.…”
Section: The Proposed Methodsmentioning
confidence: 99%
“…In this research, we explored vision-based Transformer architecture for SC classification as shown in Figure 2 , where the MVT architecture receives an image as input data with a size of 72 by 72. First, the input image is converted into patches as in [ 55 ]. MVT supports a different number of patches based on the underline scenario.…”
Section: The Proposed Methodsmentioning
confidence: 99%
“…Su et al [1] concentrated on the deep transfer learning (TL) for the recognition and categorization of FM. Habib et al [2] focused on the deep learning (DL) based model for the identification of FM.…”
Section: Related Workmentioning
confidence: 99%
“…The MobileNet model is devised for enhancing the real word outcome of the DL model with restricted hardware units (15,16) . Here, the ReLU activation function is substituted by ReLU6, and the BN process is performed, supporting the automated alteration of data distribution.…”
Section: Dlmn Based Feature Extractionmentioning
confidence: 99%